Analisis Pemanfaatan Gelombang Elektromagnetik pada WX Radar System untuk Mrnghindati Loss off Aircraft Control - Restu Dwi Setiyo Utami; Sudarti Sudarti; Yushardi Yushardi (Journal of Creative Student Research, 2023)
Loss of Aircraft Control incidents have occurred frequently in the past few years. In the last 7 years, 5 aircraft have experienced Loss of Aircraft Control. Loss of Aircraft Control itself is the disappearance of the aircraft from the monitoring radar. The causes of loss of aircraft contact include the effects of weather. In the aviation system, weather does have a very big influence. To minimize the loss of aircraft contact, each aircraft is equipped with a weather radar or what is known as the WX Radar System. WX Radar System is an example of the application of electromagnetic waves, namely radio waves that work with the principle of the doppler effect. Where the radar will emit electromagnetic waves with a low frequency which will then be reflected back by weather particles in the earth's atmosphere. The results of the reflection are then displayed in the cockpit of the aircraft so that the pilot knows the weather conditions outside the aircraft so as to avoid things that are not desired such as loss of aircraft contact or Loss of Aircraft Control.